Performa Pertumbuhan dan Ekspresi Gen Hormon Pertumbuhan Sidat (Anguilla bicolor bicolor) Stadia Elver Yang diberi Pakan Mengandung Kromium Pikolinat - Dewi Nugrayani; Anandita Ekasanti; Hamdan Syakuri; Emyliana Listiowati; Petrus Hary Tjahja Soedibya; Sri Marnani; Marhaendro Santoso; Rudy Wijaya; Purnama Sukardi; Kasprijo Kasprijo (Jurnal Akuakultur Sungai dan Danau, 2023)
The administration of chromium picolinate (Cr-Pic) is expected to positively influence the growth of eel (Anguilla bicolor) and the expression of the growth related gene. The purpose of this research was to study the effect of chromium picolinate (Cr-Pic) on the growth performance and expression of growth hormone encoding gene of eel (Anguilla bicolor), a species of fish that is in the process of domestication. The experiment consisted of four treatments: without Cr-Pic (P0), with Cr-Pic of 1 mg / kg of feed (P1), 2 mg / kg of feed (P2), and 3 mg / kg of feed (P3). Eel growth performance was analyzed based on absolute and daily growth rates. Observation of the level of growth hormone (GH) gene expression was performed using real-time RT-PCR method. The results showed that administration of Cr-Pic did not significantly increase eel growth rate. The expression level of growth hormone genes in eel fed 2 and 3 mg Cr-Pic / kg was higher than the expression level of this gene in eel fed without Cr-Pic. The results showed that the level of growth hormone expression did not appear to be related to growth rate of the eel.